2017
DOI: 10.1248/bpb.b17-00059
|View full text |Cite
|
Sign up to set email alerts
|

Supplemented Chondroitin Sulfate and Hyaluronic Acid Suppress Mineralization of the Chondrogenic Cell Line, ATDC5, <i>via</i> Direct Inhibition of Alkaline Phosphatase

Abstract: Chondroitin sulfate (CS) is a sulfated polysaccharide produced by chondrocytes. Alkaline phosphatase (ALP) is an important enzyme involved in the mineralization of chondrocytes. In recent years, it has been reported that CS regulates the differentiation of various cells. In this study, we investigated the effect of supplemented CS on ALP activity and mineralization of the chondrogenic cell line, ATDC5. In addition, hyaluronic acid (HA), a non-sulfated and acidic polysaccharide, was used in comparison to CS. CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…During chondrogenic induction, MMC significantly increased collagen type I, II, X and sulphated GAG deposition, whilst no difference in Sox-9 expression was detected. Similarly, previous studies have shown medium supplementation with sulphated polysaccharides to induce chondrogenic differentiation of stem cells (Kawamura et al, 2014) and to suppress mineralisation of a chondrogenic cell line, through direct inhibition of alkaline phosphatase, therefore maintaining their phenotype (Kudo et al, 2017). Enhanced collagen type I and X and decreased collagen type II synthesis are indicative of chondrocyte trans-differentiation and hypertrophy (Descalzi Cancedda et al, 1992;Gu et al, 2014;Kielty et al, 1985;Tekari et al, 2014;von der Mark et al, 1977;von der Mark et al, 1992;Zheng et al, 2003).…”
Section: Discussionmentioning
confidence: 81%
“…During chondrogenic induction, MMC significantly increased collagen type I, II, X and sulphated GAG deposition, whilst no difference in Sox-9 expression was detected. Similarly, previous studies have shown medium supplementation with sulphated polysaccharides to induce chondrogenic differentiation of stem cells (Kawamura et al, 2014) and to suppress mineralisation of a chondrogenic cell line, through direct inhibition of alkaline phosphatase, therefore maintaining their phenotype (Kudo et al, 2017). Enhanced collagen type I and X and decreased collagen type II synthesis are indicative of chondrocyte trans-differentiation and hypertrophy (Descalzi Cancedda et al, 1992;Gu et al, 2014;Kielty et al, 1985;Tekari et al, 2014;von der Mark et al, 1977;von der Mark et al, 1992;Zheng et al, 2003).…”
Section: Discussionmentioning
confidence: 81%
“…44,63,64 Preparation of methacrylated HA and CSC HA and CSC were selected for evaluation based on their structural role in cartilage, their chondroprotective effects, and their ability to facilitate chondrogenesis. 39,[65][66][67][68][69][70] In order to conjugate these GAGs into the PEGDA-based scaffolds, each GAG type was methacrylate-derivatized according to standard protocols. 71 In brief, CSC (51 kDa, 6.4 wt % sulfur, Sigma) and HA (Streptococcus equi, M W~1 .65 × 10 3 kDa, Fluka) were dissolved in deionized (dI)H 2 O to achieve a 1 wt % final concentration, and the pH of each solution was adjusted to 8.0.…”
Section: Methodsmentioning
confidence: 99%
“…Alkaline phosphatase is an ectoenzyme that is present on the membrane of cells and matrix vesicles. In humans, four ALP isoenzymes are present: intestinal ALP, placental ALP, germ cell ALP, and tissue-non-specific ALP expressed in bone, liver, and kidney. , ALP enzymatic activity stimulates initial mineralization in the presence of glycerolphosphate. If glycerolphosphate disappears from the solution, then mineralization of the vesicles and osteoblastic cell culture becomes impossible .…”
Section: Introductionmentioning
confidence: 99%